2022
DOI: 10.1101/2022.11.21.516512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanding the Huntington’s disease research toolbox; validated subdomain protein constructs for biochemical and structural investigation of huntingtin

Abstract: Huntington's disease is characterised by the CAG expansion in the huntingtin gene above a critical threshold of ~35 repeats, which results in the polyglutamine expansion of the huntingtin protein (HTT). The biological roles of wildtype HTT and the associated mechanisms of disease pathology caused by expanded HTT remain incompletely understood, in part due to challenges in directly characterising interactions between HTT and putative binding partners. Here we describe a biochemical toolkit of two rationally des… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It should be noted that while these results support a direct interaction, the technical constraints of the experiment preclude saturation of the binding curve and therefore determination of binding kinetics and specificity. We next tested the PAR binding ability of different huntingtin subdomain constructs [78], and found that a construct comprising the N-HEAT and Bridge domains, which contains PBM-3, binds 26-mer PAR, while the C-HEAT domain (in complex with HAP40) does not ( Fig 5B ). We did not detect a significant difference in PAR binding between wild type and mutant huntingtin, nor upon deletion of the exon 1 domain in this assay ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that while these results support a direct interaction, the technical constraints of the experiment preclude saturation of the binding curve and therefore determination of binding kinetics and specificity. We next tested the PAR binding ability of different huntingtin subdomain constructs [78], and found that a construct comprising the N-HEAT and Bridge domains, which contains PBM-3, binds 26-mer PAR, while the C-HEAT domain (in complex with HAP40) does not ( Fig 5B ). We did not detect a significant difference in PAR binding between wild type and mutant huntingtin, nor upon deletion of the exon 1 domain in this assay ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 99%